Growth differentiation factor 15 increases following oral glucose ingestion: effect of meal composition and obesity. Issue 6 (December 2016) - Schernthaner-Reiter, Marie Helene; Kasses, Dominik; Tugendsam, Christina; Riedl, Michaela; Peric, Slobodan; Prager, Gerhard; Krebs, Michael; Promintzer-Schifferl, Miriam; Clodi, Martin; Luger, Anton; Vila, Greisa
Abstract : Objective: Growth differentiation factor 15 (GDF15) is a cardiovascular biomarker belonging to the transforming growth factor-β superfamily. Increased GDF15 concentrations are associated with insulin resistance, diabetes and obesity. We investigated the physiological effects of meal composition and obesity on the regulation of systemic GDF15 levels. Design: Lean ( n = 8) and obese ( n = 8) individuals received a carbohydrate- or fat-rich meal, a 75 g oral glucose load (OGTT) or short-term fasting. OGTTs were performed in severely obese patients ( n = 6) pre- and post-bariatric surgery. Methods: Circulating serum GDF15 concentrations were studied in lean and obese individuals in response to different meals, OGTT or short-term fasting, and in severely obese patients pre- and post-bariatric surgery. Regulation of GDF15 mRNA levels and protein release were evaluated in the human hepatic cell line HepG2. Results: GDF15 concentrations steadily decrease during short-term fasting in lean and obese individuals. Carbohydrate- and fat-rich meals do not influence GDF15, whereas an OGTT leads to a late increase in GDF15 levels. The positive effect of OGTT on GDF15 levels is also preserved in severely obese patients, pre- and post-bariatric surgery. We further studied the regulation of GDF15 mRNA levels and protein release in HepG2, finding that glucose and insulin independently stimulate both GDF15 transcription and secretion. Conclusion: In summary, high glucose and insulin peaks upregulate GDF15 transcription and release. The nutrient-induced increase in GDF15 levels depends on rapid glucose and insulin excursions following fast-digesting carbohydrates, but not on the amount of calories taken in.